Non conventional biological treatment based on Trametes versicolor for the elimination of recalcitrant anticancer drugs in hospital wastewater. (October 2015) - Ferrando-Climent, Laura; Cruz-Morató, Carles; Marco-Urrea, Ernest; Vicent, Teresa; Sarrà, Montserrat; Rodriguez-Mozaz, Sara; Barceló, Damià
Highlights: Removals from 48 till 100% of anticancer drugs in hospital effluent treated by fungi. Cyclophosphamide and Ifosfamide remained unalterable whereas Tamoxifen was totally removed. Two hydroxilated positional isomers of Tamoxifen detected for first time in treated effluents. Abstract: This work presents a study about the elimination of anticancer drugs, a group of pollutants considered recalcitrant during conventional activated sludge wastewater treatment, using a biological treatment based on the fungus Trametes versicolor. A 10-L fluidized bed bioreactor inoculated with this fungus was set up in order to evaluate the removal of 10 selected anticancer drugs in real hospital wastewater. Almost all the tested anticancer drugs were completely removed from the wastewater at the end of the batch experiment (8 days) with the exception of Ifosfamide and Tamoxifen. These two recalcitrant compounds, together with Cyclophosphamide, were selected for further studies to test their degradability by T. versicolor under optimal growth conditions. Cyclophosphamide and Ifosfamide were inalterable during batch experiments both at high and low concentration, whereas Tamoxifen exhibited a decrease in its concentration along the treatment. Two positional isomers of a hydroxylated form of Tamoxifen were identified during this experiment using a high resolution mass spectrometry based on ultra-high performance chromatography coupled to an Orbitrap detector (LTQ-Velos Orbitrap). Finally the identified transformation products of Tamoxifen were monitored in the bioreactor run with real hospital wastewater.